2000
DOI: 10.1093/sw/45.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Court-Ordered Substance Abuse Treatment in Child Protective Services Cases

Abstract: Courts often play active roles in the lives of families supervised by child protective services (CPS). Judges adjudicate dependency, mandate services, determine placements of children, and order continued supervision or termination of parental rights or services. This study examined the effects of court orders in preventing recurrence of substance abuse in the cases of 447 children in kinship care while under CPS supervision. In addition, the effects of court orders on duration of service and on numbers of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 10 publications
4
34
0
Order By: Relevance
“…Finding effective reading intervention strategies is necessary for students who are EBD (Ishii-Jordan, 2000) because there is a strong correlation between reading failure and school failure (Scott & Shearer-Lingo, 2002). Students with EBD are especially at risk for reading difficulties when they have other disabilities such as learning disabilities or attention deficit disorder (Rittner & Dozier, 2000). The NEP (2000) Repeated readings involves the reader repeatedly reading a short passage of usually no more than 200 words until fluency is achieved (Samuels, 1979;Stahl & Heubach, 2005;Therrien & Kubina, 2006).…”
Section: Chapter Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Finding effective reading intervention strategies is necessary for students who are EBD (Ishii-Jordan, 2000) because there is a strong correlation between reading failure and school failure (Scott & Shearer-Lingo, 2002). Students with EBD are especially at risk for reading difficulties when they have other disabilities such as learning disabilities or attention deficit disorder (Rittner & Dozier, 2000). The NEP (2000) Repeated readings involves the reader repeatedly reading a short passage of usually no more than 200 words until fluency is achieved (Samuels, 1979;Stahl & Heubach, 2005;Therrien & Kubina, 2006).…”
Section: Chapter Summarymentioning
confidence: 99%
“…Teachers have reported that fear of failure was so entrenched in students with EBD that these students often refused to participate in reading or to complete reading-related activities unless they were assured that they would succeed at the task (Atkinson, Wilhite, Frey, & Williams, 2002). Students with EBD are especially at risk for reading difficulties when they also have other disabilities such as learning disabilities or attention deficit disorder (Rittner & Dozier, 2000). As reported by Blumberg et al, 2003, more than half of the students (51.7%) who are labeled with an EBD, also have a learning disability making it necessary to differentiate their reading instruction in order to meet their academic needs.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal problematic substance use, particularly among women of lower socioeconomic status, increases the likelihood of child welfare involvement (Rittner & Davenport-Dozier, 2000;Semidei, Radel & Nolan, 2001;Trocme et al, 2005). Increased likelihood of involvement is especially true for single mothers and Aboriginal women (Boyd, 1999;Blackstock, Trocme, & Bennett, 2004).…”
Section: The Problem and Research Objectivesmentioning
confidence: 99%
“…A lack of social worker training in screening for problematic substance use and related problems interferes with thorough assessment of the family's functioning. Consequently, this lack of training also interferes with early and appropriate intervention (Dore, Doris, & Wright, 1995;Rittner & Davenport-Dozier, 2000).…”
Section: The Problem and Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation